Identification and characterisation of candidate monoclonal antibody Ebolavirus therapeutics - Donnellan, FR (2021)
Multiple species of Ebolaviruses can cause outbreaks of devastating disease with high mortality. The 2014 outbreak in West Africa, focused attention on efforts to develop effective vaccines and therapies to save lives. Since then, vaccines and first generation therapies have been developed and approved for use. The only therapies to have shown any efficacy in human clinical trials are monoclonal antibodies (mAbs) targeting the Glycoprotein (GP) on the virus surface. However, they are limited in potency and breadth of activity as they target only Zaire ebolavirus (EBOV), yet Sudan ebolavirus (SUDV), Bundibugyo ebolavirus (BDBV) and Tai Forest ebolavirus (TAFV) also cause human disease. The aims of this thesis were to generate a panel of mAbs that could bind to GP from all species of Ebolaviruses that cause human disease, then to characterise the mAbs to select candidates to enter the pipeline of next generation therapies progressing to in vivo study. Using high throughput methods a panel of nineteen anti-GP mAbs were isolated, six of which could recognise GP from all four Ebolaviruses that have caused human disease. These mAbs were characterised in a range of in vitro assays focusing on their ability to neutralise pseudoviruses coated with Ebolavirus GPs. The panel of mAbs was subjected to a range of complementary biochemical assays to map their epitopes, and the epitope of one mAb, 11886, was characterised in more detail. 11886 is of interest to progress to in vivo study as it is able to neutralise all pseudoviruses so far tested and investigation of its epitope suggests that it binds a similar footprint to other broadly protective mAbs in the literature, but neutralises the virus via a different mechanism or mode of binding.